2015
DOI: 10.1111/jpc.12948
|View full text |Cite
|
Sign up to set email alerts
|

Dog bites to the upper extremity in children

Abstract: Dog bites at the upper extremity are more prone to require surgical intervention and develop infection than those at the lower extremity, and delayed presentation of these injuries is associated with higher incidence of developing infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…The increased frequency of dog bites to the face in younger children has been noted in hospital‐based studies . In contrast, the decreased frequency of extremity dog bites is highlighted by a retrospective study in a paediatric population which found that only 22.4% of dog bites involved the upper extremity and 35% involved the lower extremity .…”
Section: Discussionmentioning
confidence: 98%
“…The increased frequency of dog bites to the face in younger children has been noted in hospital‐based studies . In contrast, the decreased frequency of extremity dog bites is highlighted by a retrospective study in a paediatric population which found that only 22.4% of dog bites involved the upper extremity and 35% involved the lower extremity .…”
Section: Discussionmentioning
confidence: 98%
“…4a). Several authors [14, 21, 32, 33] have noted that children are more likely to sustain bites to the head and neck, while adults are more likely to sustain bites to the extremities. However, a breakdown of anatomic location by detailed age groups has not been described until now.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pattern is variable, most injuries due to severe dog bites were on the head, neck or shoulders [7] in adults and head, neck and upper extremity in children [12] , [13] . Most injuries involved bony and soft tissue trauma [14] but tendon, nerve and vascular injuries were also noted and of all bites causing tendon dysfunction, nerve palsy and vascular trauma, most of these canine bites were on the forearm [15] .…”
Section: Discussionmentioning
confidence: 99%
“…The most common type of vessel trauma due to a canine bite was an occlusion (60%) [15] , but there are usually two components of a dog bite, a penetrating injury usually causing puncture or laceration to the vessel and a blunt one which may be the more clinically significant injury [13] . Superficial dog bites in children can present in a delayed fashion as well following blunt arterial trauma [19] and one can define a crush injury as a maceration or contusion of the artery [14] with a laceration causing a partial or complete transection (as in our Case1, the axillary vein).…”
Section: Discussionmentioning
confidence: 99%